Amine‐Functionalized Spin Crossover Building Blocks. Issue 43 (13th November 2019) - Flötotto, Henrik; Secker, Tim; Kögerler, Paul; Besson, Claire
Abstract: Invited for the cover of this issue is the group of Paul Kögerler from RWTH Aachen University, Germany. The cover image shows an aluminum sheet painted with thermochromic lacquer based on functionalized derivatives of iron(II) bis(tris(pyrazolyl)borate) complexes. Abstract : In addition to their originally intended use as switching components for molecular electronics, the synthesized complexes can also be used as color pigments in thermochromic coatings … Read more about the story behind the cover in the Cover Profile and about the research itself in the Communication by P. Kögerler, C. Besson et al.